2024
DOI: 10.1002/jctb.7601
|View full text |Cite
|
Sign up to set email alerts
|

ZnO nanomaterials with enhanced antimicrobial activity obtained by Eichhornia crassipes aqueous extract‐mediated synthesis

Rosendo López González,
Mirian Hernández Gutiérrez,
Ruth Lezama García
et al.

Abstract: BackgroundZinc oxide nanoparticles (ZnO NPs) were obtained through precipitation synthesis, using aqueous water hyacinth leaf extract (Eichhornia crassipes) under alkaline conditions. The effect of the extract on the physicochemical and antimicrobial properties of the ZnO was evaluated starting from concentrated extract (labeled as E100) and performing two dilutions of this concentrated extract at 50 and 25% in water (E50, and E25).ResultsThe FTIR spectra revealed, strong peaks around 3440 cm‐1, corresponding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…This is reflected in the presence of bands in the FTIR spectrum attributed to organic residues even after calcination, as demonstrated by Matinise et al [ 21 ] in the formation of ZnO with Moringa oleifera extract, where phytochemicals leave Zn 2+ metal ions chelated and stabilized during the calcination process. According to previous work [ 11 ], the aqueous extract of E. crassipes contains polyphenols and flavonoids, which are lightweight volatile compounds. Although the mechanism of extract-mediated synthesis has not been fully understood, it has been assumed that amine and carboxylic groups from the plant extract may adsorb onto the surface of the as-synthesized ZnO particles, as reported with the extract from Nigella sativa seeds [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is reflected in the presence of bands in the FTIR spectrum attributed to organic residues even after calcination, as demonstrated by Matinise et al [ 21 ] in the formation of ZnO with Moringa oleifera extract, where phytochemicals leave Zn 2+ metal ions chelated and stabilized during the calcination process. According to previous work [ 11 ], the aqueous extract of E. crassipes contains polyphenols and flavonoids, which are lightweight volatile compounds. Although the mechanism of extract-mediated synthesis has not been fully understood, it has been assumed that amine and carboxylic groups from the plant extract may adsorb onto the surface of the as-synthesized ZnO particles, as reported with the extract from Nigella sativa seeds [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that extracts from this plant are effective in the synthesis of ZnO NPs using various precursors. For instance, using zinc nitrate with the extract of this plant not only improves the optical and morphological properties of the NPs [ 9 ] but also, when using zinc acetate, enhances their antimicrobial activity [ 10 , 11 ]. This study focuses on evaluating the antifungal properties of ZnO NPs assisted by E. crassipes extract, analyzing different concentrations of the extract and their impact on the physical and chemical properties of ZnO.…”
Section: Introductionmentioning
confidence: 99%